Technological Progress, Inequality and Entrepreneurship From Consumer Division to Human Centricity - Ratten, Vanessa (Studies on Entrepreneurship, Structural Change and Industrial Dynamics, 2020)
XIV, 138 p. 14 illus., 5 illus. in color.